Power reduction quadrant-based directional routing protocol (Q-DIR) in mobile ad hoc network - A. Latif, Liza (2007)
Flooding of request packet in the route discovery phase in Mobile Ad Hoc Network (MANET) creates a broadcast storm which increases the probability of packet collisions. With location information of the destination node, the source node and also of the current node, route request will be more directed towards destination since nodes that are within the directed region will participate in the routing process. Hence, nodes that are out of the trajectory will ignore the packet and thus reduces the number of broadcasting nodes and consequently, less probability of collisions. This paper presents Quadrant- based directional routing protocol (Q-DIR) algorithm that limits the broadcast region to a quadrant where the destination node and source node are located. Q-DIR utilizes location information of the destination node, the source node and the current node. With Q-DIR as a reactive routing protocol, routing overhead will be reduced and consequently, reduces total network power consumption through limited flooding. This paper will present the performance of Q-DIR in a densely populated network of 49 nodes.